2022
DOI: 10.3390/ani12223220
|View full text |Cite
|
Sign up to set email alerts
|

Hazelnut Skin in Ewes’ Diet: Effects on Colostrum Immunoglobulin G and Passive Transfer of Immunity to the Lambs

Abstract: Passive immunity transfer has a pivotal role in newborn lambs, where the colostrum represents the primary source of immunoglobulins. This study hypothesized that the high content in polyphenolic compounds, mono- and poly-unsaturated fatty acids, and vitamin E of hazelnut skin affects blood and colostrum immunoglobulin G (IgG) concentration and related gamma-glutamyl-transferase (GGT) and lactate dehydrogenase (LDH) levels in sheep and their lambs. In the last 45 days of pregnancy, ewes were divided into a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…IgA has a better immune function in the local mucosa of the respiratory tract and digestive tract and infected membrane tissue [30]. IgG is the main antibody in serum, accounting for about 75% of immunoglobulins, and it has the function of binding antigens to activate, complement, and kill pathogens to resist infection effectively [31]. IgG is the main component of antibacterial, antitoxin, and antiviral antibodies and is also an important material that provides dairy cows protection against infection.…”
Section: Discussionmentioning
confidence: 99%
“…IgA has a better immune function in the local mucosa of the respiratory tract and digestive tract and infected membrane tissue [30]. IgG is the main antibody in serum, accounting for about 75% of immunoglobulins, and it has the function of binding antigens to activate, complement, and kill pathogens to resist infection effectively [31]. IgG is the main component of antibacterial, antitoxin, and antiviral antibodies and is also an important material that provides dairy cows protection against infection.…”
Section: Discussionmentioning
confidence: 99%
“…Sufficient energy to the dam is ingesting and whether that meets its gestational requirements [44,45]. Viola et al [46] have shown that ewe's diet in the last period of gestation can effect colostral IgG concentration; for instance hazelnut skin in ewe's diet effects positively colostral IgG concentration. Under that condition, colostrum quality is associated directly to the dam's nutrition.…”
Section: Factors Up To Dammentioning
confidence: 99%
“…Sufficient energy to the dam is ingesting and whether that meets its gestational requirements (Banchero et al, 2006;Muñoz et al, 2008). Viola et al (2022) have indicated that an ewe's diet in the last period of gestation can effect colostral IgG concentration; for instance hazelnut skin in ewe's diet effects positively colostral IgG concentration. Under that condition, colostrum quality is associated directly to the dam's nutrition.…”
Section: Why Pit Is Crucial?mentioning
confidence: 99%